Soviet cinema (Mass culture and entertainment in Russia., 2007)
The collection includes Soviet film magazines from the 1920s and 1930s, reflecting an interesting and fertile period in the history of Russian film. Film publications were revived in the early 1920s after being interrupted in 1918 by Bolshevik censorship. In the beginning, the film press offered detailed coverage of the industry, both in the USSR and abroad, in addition to advertising western films playing on Soviet screens. By the end of the 1920s, a partial and eventually complete ban on imported films was introduced, marking the beginning of a campaign to "proletarize" Soviet art. By the mid-1930s, ideological consensus and Socialist Realism as the dominant mode in art came to the fore in film, as in all other areas of Soviet art.